Positive health beliefs are associated with improvement of glycated hemoglobin and lipid profiles in Mexican patients with type 2 diabetes mellitus: a cross-sectional study - Abril Violeta Muñoz-Torres; Patricia Medina-Bravo; Brenda Elizabeth Valerio-Pérez; Grecia Mendoza-Salmeron; Jorge Escobedo-de la Peña; Lubia Velázquez-López (BMC, 2020)
Abstract Background Health beliefs are relevant to consider in patients with type 2 diabetes since disease control depends mainly on the patient's behaviour. The aim of this study was to assess the association between health beliefs and glycated hemoglobin levels in Mexican patients with type 2 diabetes. Methods An analytical cross-sectional study was conducted, and 336 patients were included. Fasting blood levels of glycated hemoglobin, glucose, cholesterol; triglycerides, high-density lipoprotein cholesterol (HDL-c), and low-density lipoprotein cholesterol (LDL-c) were measured. Body fat percentage, weight, height; waist circumference, and systolic and diastolic blood pressures were also obtained. A previously validated self-administered questionnaire was used to assess the health beliefs with regards to non-pharmacological treatment. Health beliefs were classified as positive, neutral, and negative. Results The average age of patients was 54.7 ± 8.5 years, with a higher proportion of females (69%). The questionnaire had a good internal consistency with a Cronbach's alpha score of 0.83. More than 90% of patients attributed a health benefit to diet and exercise, 30 to 40% experienced barriers, and more than 80% had a perception of complications associated to uncontrolled diabetes. Patients with positive health beliefs had lower HbA1c levels (8.2 ± 1.7%) compared to those with neutral (9.0 ± 2.3%), or negative (8.8 ± 1.8%; p = 0.042). The LDL-c levels were lower (p = 0.03), and HDL-c levels were higher (0.002) in patients with positive heath beliefs. Conclusions Positive health beliefs are associated with better metabolic control indicators in patients with type 2 diabetes.